Kikuchi-Fujimoto Disease in a Young Female: A Case Report - Dewi, Ni Putu Merlynda Pusvita (Riviera Publishing, 2025)
Kikuchi-Fujimoto Disease (KFD) is an uncommon, non-cancerous inflammatory condition of the lymph nodes that typically affects young women of Asian descent. It often manifests through vague clinical signs such as fever and swollen lymph nodes in the neck, which can easily be mistaken for more serious illnesses, including lymphoma or systemic lupus erythematosus (SLE). The difficulty in diagnosis is heightened by the lack of distinctive features on imaging studies, making histopathological examination via lymph node biopsy vital for establishing a definitive diagnosis and preventing incorrect treatment. This case involves a 25-year-old woman who experienced persistent fever and multiple painful cervical lymph nodes for two weeks. Blood tests indicated mild anemia and an increased erythrocyte sedimentation rate (ESR). Ultrasound revealed several solid, avascular nodules, and biopsy findings confirmed the presence of KFD. Treatment focused on symptom relief using non-steroidal anti-inflammatory drugs (NSAIDs), resulting in full recovery within a fortnight. Due to the disease’s possible links with autoimmune conditions and its tendency to recur, ongoing monitoring of patients is essential. This case highlights the necessity of precise identification to avoid overtreatment and calls attention to the importance of further studies on KFD’s underlying mechanisms, potential early diagnostic markers, and long-term patient outcomes to enhance clinical care.